Criteria for evaluating a novel - Švajncer, Marija (Slavia Centralis, 2022)
The article discusses the criteria for the evaluation of novels. We demonstrate the terminology, the problem of definition, and the findings of classical Slovenian literary historians, as well as contemporary views on reading and evaluating novels. Arguments put forward form the basis for thinking about the relativity of evaluation and the possibilities of loose assessment. Finally, we provide an example of the analysis and evaluation of a contemporary Slovenian novel, and thus the application of our theoretical knowledge to a concrete work of prose.